2008
DOI: 10.1105/tpc.108.058768
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant Impaired in the Production of Plastome-Encoded Proteins Uncovers a Mechanism for the Homeostasis of Isoprenoid Biosynthetic Enzymes inArabidopsisPlastids

Abstract: The plastid-localized methylerythritol phosphate (MEP) pathway synthesizes the isoprenoid precursors for the production of essential photosynthesis-related compounds and hormones. We have identified an Arabidopsis thaliana mutant, rif1, in which posttranscriptional upregulation of MEP pathway enzyme levels is caused by the loss of function of At3g47450, a gene originally reported to encode a mitochondrial protein related to nitric oxide synthesis. However, we show that nitric oxide is not involved in the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
200
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(216 citation statements)
references
References 47 publications
11
200
0
5
Order By: Relevance
“…Furthermore, a recombinant version of the bacterial YqeH protein was active in complementing the mutant nos1/rif1 phenotype when fused to the N-terminal targeting peptide of the NOA1/RIF1 protein (Sudhamsu et al, 2008) or when specifically targeted to plastids (Flores-Pé rez et al, 2008) but not when targeted to mitochondria (Figure 1). In agreement with the YqeH-like activity of the NOA1/RIF1 protein being required only in plastids, the ultrastructure of etioplasts and chloroplasts but not mitochondria was affected in rif1 seedlings (Flores-Pé rez et al, 2008). These results, together with the observed decrease in the levels of proteins encoded by the plastid genome (plastome) in rif1 chloroplasts (Flores-Pé rez et al, 2008), suggest that NOA1/RIF1 might bind plastidial ribosomes and be required for their normal function and therefore for proper protein synthesis in plastids.…”
Section: Noa1/rif1 Is a Plastidial Gtpase Not Directly Related To No supporting
confidence: 64%
See 3 more Smart Citations
“…Furthermore, a recombinant version of the bacterial YqeH protein was active in complementing the mutant nos1/rif1 phenotype when fused to the N-terminal targeting peptide of the NOA1/RIF1 protein (Sudhamsu et al, 2008) or when specifically targeted to plastids (Flores-Pé rez et al, 2008) but not when targeted to mitochondria (Figure 1). In agreement with the YqeH-like activity of the NOA1/RIF1 protein being required only in plastids, the ultrastructure of etioplasts and chloroplasts but not mitochondria was affected in rif1 seedlings (Flores-Pé rez et al, 2008). These results, together with the observed decrease in the levels of proteins encoded by the plastid genome (plastome) in rif1 chloroplasts (Flores-Pé rez et al, 2008), suggest that NOA1/RIF1 might bind plastidial ribosomes and be required for their normal function and therefore for proper protein synthesis in plastids.…”
Section: Noa1/rif1 Is a Plastidial Gtpase Not Directly Related To No supporting
confidence: 64%
“…A plastidial localization was recently reported for the diatom NOA1 homolog (Vardi et al, 2008). The untagged Arabidopsis protein was imported into isolated wild-type chloroplasts, whereas a GFP fusion that fully rescued the rif1 phenotype was found to be localized in chloroplasts (Flores-Pé rez et al, 2008). Substitution of the putative N-terminal organelle-targeting sequence of the NOA1/RIF1 protein by a previously characterized plastid-targeting sequence resulted in a chimeric protein that was able to restore fosmidomycin sensitivity and normal greening and growth when expressed in rif1 plants (Figure 1).…”
Section: Noa1/rif1 Is a Plastidial Gtpase Not Directly Related To No mentioning
confidence: 76%
See 2 more Smart Citations
“…Recently, it has been found that enzymes of the MEP pathway require posttranslational modification, such as can be seen in the stromal ClpPR proteolytic complex. 48 Therefore, it is possible that the AMOS1/ EGY1 metalloprotease activates MEP pathway enzymes in such a manner, modulating MEcPP levels, to regulate the expression of ammonium-stress-responsive genes in the nucleus.…”
Section: Interaction Of Plastid Retrograde Signaling and Aba Signalinmentioning
confidence: 99%